Desenvolvimento de uma nova plataforma para detecção de mioglobina empregando ressonância de plásmons de superfície e medidas eletroquímicas - Carvalho, Rita de Cassia Silva (2016)
Cardiovascular diseases (CVDs) are considered as an important cause of morbidity and premature mortality worldwide. Rapid diagnosis of CVD is extremely important to ensure the survival of the patient. Myoglobin (Mb), for its low molecular weight is quickly released in the body, resulting in high sensitivity in order to be as valuable biomarker of acute myocardial infarction (AMI). Therefore, this study aims to develop an efficient platform, sensitive and stable for the immobilization of antibodies (Ab) myoglobin applicable to the monitoring of antigens (Ag) myoglobin using surface plasmon resonance (SPR). In this sense, the cyclic voltammetry, differential pulse voltammetry and impedance spectroscopy were used in selfassembled monolayers research (SAMs) simple and mixed acid 11-mercaptoundecanoic (MUA) and 3-mercaptopropionic acid (MPA). The mixed SAM MPA / MUA 3: 1 ratio showed low resistance to charge transfer and high surface coverage. In order to investigate the SAM capacity MPA / MUA opposite the locking Ac-MB were made comparative studies for the evaluation of the interaction of Ac-MB SAM MPA / MUA well as for SAM MPA / MUA modified polyamidoamine dendrimer of generation 5 (G5 PAMAM). Then, after choosing the more sensitive platform made up AC-Mb interaction studies with different concentrations of Ag-Mb (0,001; 0,5; 0,8; 1 and 500 µg.mL-1) through immunoassay in a "sandwich". The three-dimensional structure of the dendrimer PAMAM G5 favored amplification of SPR signal as grants most accessible area for the immobilization of antibody Mb. The sandwich immunoassay amplified the interaction signal Ac / Ag Mb, with significant advantages in sensitivity immunosensor. The results show that it was possible to develop an immunosensor capable of detecting low concentrations (0.00067 μg.mL-1) Ag-Mb. In this sense, the proposed system has great potential alternative to early diagnosis, simple and fast IAM.